Analyzing publishing trends in information literacy literature: A bibliometric study - Shaheen, Majid; Chang, Yun-Ke; Hnin Nu, Aye; Ma May Win, Khine; San, Yu Wai; Majid, Shaheen; Chang, Yun-Ke; Aye, Hnin Nu; Khine, Ma May Win; San, Yu Wai (Malaysian Journal of Library and Information Science, 2017)
Majid, S., Chang, Y. K., Hnin, N. A., Ma, M. W. K., & San, Y. W. (2015). Analyzing publishing trends in information literacy literature: A bibliometric study. Malaysian Journal of Library & Information Science, Vol.20, no. 2: 51-66. The main objective of this study was to explore scholarly communication trends in the field of information literacy. A total of 1989 records from Scopus bibliographic database, published from 2003 to 2012, were analyzed. The Scopus database was preferred over the Web of Science as it provided considerably more hits for the phrase ‘information literacy’. Other possible synonyms for the concept of information literacy were ignored to minimize the retrieval of irrelevant documents. MS Excel as well as specific Scopus analytical tools were used for data analysis. Some areas covered in the data analysis included: annual growth in information literacy publications, preferred journals for publishing information literacy articles, most prolific authors, top countries producing information literacy literature, and publication distribution by subject. It was found that the number of information literacy publications have increased steadily during the last ten years. It was also revealed that a majority of information literacy publication were written by authors from North America and the United Kingdom.